Comparative effects of selenium-enriched lactobacilli and selenium-enriched yeast on performance, egg selenium enrichment, antioxidant capacity, and ileal microbiota in laying hens - Zhou, Jianmin; Obianwuna, Uchechukwu Edna; Zhang, Longfei; Liu, Yongli; Zhang, Haijun; Qiu, Kai; Wang, Jing; Qi, Guanghai; Wu, Shugeng (Journal of animal science and biotechnology, 2025)
Organic selenium (Se) has gained recognition in poultry nutrition as a feed additive to boost production and Se deposition in eggs and tissues, owing to its high bioavailability, efficient tissue accumulation and minimal toxicity. Selenium-enriched yeast (SeY) is a well-established source, while selenium-enriched lactobacilli (SeL), a newer alternative, offers the added benefits of probiotics. This study examined the effects of SeY and SeL on egg quality, antioxidant capacity, Se deposition, and gut health in laying hens. After a two-week pre-treatment with a Se-deficient diet (SeD), 450 Hy-Line Brown laying hens (30-week-old) were assigned into five dietary groups with six replicates of 15 hens each. The groups included a SeD, SeD supplemented with 1.5 mg Se/kg from SeY (SeY15), or 1.5, 3.0, and 6.0 mg Se/kg from SeL (SeL15, SeL30, SeL60). The feeding trial lasted for 12 weeks. SeY15 and SeL15 improved the feed-to-egg ratio (P < 0.05) in the latter stages. Haugh units were significantly increased (P < 0.05) in the SeY15 and SeL30 groups, while darker yolk color (P < 0.05) was observed in the SeY15, SeL15, and SeL60 groups. All Se-supplemented diets increased Se content in whole eggs, albumen, and yolk (P < 0.05), while SeL groups showed a dose-dependent effect. Antioxidant enzyme activities increased, and MDA content decreased in the serum (P < 0.05), with SeY15 showing the highest GSH-Px levels (P < 0.05). SeL60 increased serum alkaline phosphatase and aspartate transaminase, and distorted the liver architecture (P < 0.05). Se-diets reduced concentrations of reactive oxygen species (ROS) in the ileum and liver (P < 0.05). SeL15 improved the ileal villus height-to-crypt depth ratio (P < 0.05). SeY15 and/or SeL15 up-regulated TXNRD1 and SEPHS1 mRNA while down-regulating SCLY expression in the liver. SeY15 altered ileal microbiota by increasing both beneficial and pathogenic bacteria, whereas SeL15 predominantly boosted beneficial bacteria. SeL integrates the antioxidant properties of organic Se with the probiotic benefits on gut health, resulting in a performance-enhancing effect comparable to that of SeY. However, high SeL level (6.0 mg Se/kg) compromised productivity and metabolic functions while enhancing Se deposition.